Pengungkapan Kejahatan Hacking Mengakses Sistem Elektronik Milik Orang Lain Di Wilayah Hukum Polres Batanghari - Muslih, Muhammad; Sahabuddin, Said; Tanzil, Tanzil (Universitas Batanghari Jambi, 2023)
Cybercrime is a whole form of crime directed against computers, computer networks and their users, and conventional forms of crime using or with the help of computer equipment. The purposes of this study are To understand and analyze the disclosure of hacking crimes by accessing other people's electronic systems in the Batanghari Police area. To understand and analyze the obstacles in disclosing the crime of hacking accessing electronic systems belonging to other people in the Batanghari Police Legal area. To understand and analyze efforts to overcome obstacles in disclosing hacking crimes by accessing other people's electronic systems in the Legal area of the Batanghari Police. The specification of this research is descriptive analytical research. In writing this thesis, the writer used a Juridical Empirical research type, while the approach used was Socio-Legal Research. The sampling technique was carried out by purposive sampling. It was revealed that the suspect sent a message to AI to instruct him to send money by transfer and then the AI replied that the money had been transferred. Then it can be concluded that the suspect has been charged with Article 30 paragraph (1) in conjunction with Article 46 paragraph (1) of the Law of the Republic of Indonesia Number 19 of 2016 which carries a maximum prison sentence of 6 years and/or a maximum fine of Rp. 600,000. 000.00.-. The obstacles faced include the case file was returned by the prosecutor, the perpetrator was not cooperative during the examination, expert witnesses were present. Regarding the efforts made to overcome obstacles, including Batanghari Resort Police Criminal Investigators have complied with the Attorney's request by including elements of Article 46 paragraph 1 of the Law of the Republic of Indonesia Number 19 of 2016, Investigators are trying to ensure that if the perpetrator is honest in giving information and willing to cooperate, the perpetrators will get relief in terms of criminal penalties, The Satreskrim of the Batanghari Police have made efforts in the form of providing suggestions in terms of assisting the investigation process, the Batanghari Police have prepared at least 1 person who can be appointed as an expert in 1 district Batanghari. Suggestions put forward that apart from investigators at the Polda level, investigators at the Polres level must also be obliged to take part in training (Dikjur) Criminal Information and Electronic Transactions in order to be able to master, understand and have special expertise or skills in the field of information and electronic transactions, then so that the investigative members no longer need a long time for the investigation process